Outcome of Preoperative Administration of Oral Ambrisentan on Pulmonary Hypertension After Cardiac Surgery for VSD (KYAMC Journal, 2020)
Background: There is significant difference between the survival of patient with and without post-operative pulmonary arterial hypertension (PAH). This study was designed to see the early post-operative outcomes of PAH after preoperative oral administration of ambrisentan.Objective: Evaluation of role of preoperative oral ambrisentan for the management of PAH following cardiac surgery for ventricular septal defect (VSD) with moderate to severe PAH.Materials and Methods: A total of 54 patients were stratified into two equal groups (n=27) depeding upon receiving of orala mbisentan. Ambrisentan group received dose of 2.5mg and 5mg in two divided doses for weight 20 kg respectively at least two weeks before surgery.Results: PASP was measured peroperatively before establishment of CPB, immediately after VSD closure and after weaning from CPB which were 59.55±11.16 mm of Hg, 45.49±9.46 mm of Hg and 40.49 ±10.33 mm of Hg respectively in the ambrisentan group (Group-A) and was 71.92 ±10.62 mm of Hg, 66.34±10.22 mm of Hg and 62.14 ±9.46 mm of Hg respectively in the control group (Group-B) with a p value of 0.002, 0.001 and 0.001 respectively. Considering PASP on echocardiogram at 7th post-operative day was 33.55 ± 1.23 in ambrisentan group and 41.70 ± 5.60 in control group. At one month PASP on echocardiogram was 30.55±2.26 in ambrisentan group and 39.11 ±3.28 in control group.Conclusion: Preoperative oral administration of ambrisentan is more effective in control of postoperative PAH and may be advised in every patients with VSD with moderate to severe PAH.KYAMC Journal Vol. 11, No.-1, April 2020, Page 36-41